Experimental Studies On Rumeno-Rectal Fistula In Calves - Sumangala M (Department of Surgery, College of Veterinary and Animal Sciences, 1980)
Chronic tympany of the rumen is common in cattle. Rumen fistulation has been reported to be successful in the treatment of chronic tympany. Left side external fistulation of rumen has been adopted by many workers. But this was accompanied by seepage of rumen contents and soiling of the flank. While screening the available literature, no reports on an internal rumen fistulation could be found.